Formation of Muslim communities in the Russian Far North: problems of adaptation and the birth of new identities - Arbakhan K. Magomedov; Magomedemin М. Gadzhiev (Historical Ethnology, 2024)
The article examines how migration processes to the Far North regions have led to the creation of Islamic communities, Muslim infrastructure and new identities in cities in the regions of the Russian Arctic. The work is based on a number of field studies conducted by the author in 2018, 2019 and 2022 in Russian polar cities, as a result of which valuable empirical materials were obtained. It is important to emphasize that Muslim communities in the cities of the Russian Far North do not give the impression that they are a part of the global Islamic Ummah. Connections with the rest of the Muslim world are limited. This does not mean that the Islamic communities of the Far North are autonomous. As in the Soviet period, control of the state over the religious space is still powerful. The authors show that Muslim communities are gradually adapting religious practices to circumpolar conditions. For many Muslim migrants, it is extremely important to be a part of Islamic networks and communities in order to survive and adapt to new conditions. These studies indicate the plasticity of the emerging identity in the minds of the Muslims in the Arctic. What is new is that the "Northerner" factor occupies a certain place in the scale of identification features of polar Muslims. The analysis shows that integration into the large northern community is a more appropriate concept than extremism or resistance when it comes to Muslims in the Russian Arctic. This is due to the fact that Islamic identity includes a fairly wide range of socially possible practices related to adaptation to northern conditions.